Sosialisasi Lingkungan Sehat Bebas dari Sampah dan Vektor Penyakit dengan Konsep Pemberdayaan Masyarakat - Anhar Fazri; Darmawan Darmawan; Arif Iskandar; Al Zuhri; Saiful Amri; Futri Syam (Universitas Teuku Umar, 2023)
The environment is one of the elements that cannot be separated from social life, whether in a crowded place or not. However, waste will be a source that significantly affects the community environment, both directly and indirectly. Garbage will become a medium for disease-carrying vectors, both organic and inorganic waste. This community empowerment-based service activity is carried out as a form of academic participation in the utilization and management of waste, which can be used as a commercial goal. Public education and awareness about the importance of good waste management are also crucial in preventing diseases caused by waste. By understanding the potential hazards associated with waste and adopting environmentally friendly practices, communities can help reduce the risk of spreading waste-related diseases. The implementation method is done through socialization through material delivery, followed by a question-and-answer process. Then several forms of waste utilization and management are carried out. The results of community service based on community empowerment are, first, providing an understanding to the public of the importance of protecting the environment from disease vector carrier waste. Second, waste can be used and managed for commercial and personal purposes and collaboration with related parties.